2022
DOI: 10.1172/jci.insight.152357
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites enhance innate resistance to human Mycobacterium tuberculosis infection

Abstract: We characterized the phenotype and function of various immune cells in a large group of LTBI -HHCs (nonconverters) of patients with TB (a total of 452 individuals). We performed these measures at baseline (0 months) and follow-up (24 months) while monitoring the participants for conversion to LTBI. By following a large cohort of HHCs of patients with TB and performing transcriptional and metabolomic studies, we determined whether resistance to M. tuberculosis infection is preceded by specific changes in the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…The most extensively studied is an NK cell memory population co-expressing NKG2C and CD57 that expands in blood during human cytomegalovirus (CMV) infection ( 27, 46 ). Multiple putative markers of NK cell memory during Mtb infection have been suggested, including CD57, CD8α, CD161, and CD27 ( 28, 34, 45 ). We compared expression of these markers across clinical groups and found that household-associated LTBI (IGRA+ contacts) and active TB disease donors had progressively decreasing frequency of CD8α + CD56 dim NK cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The most extensively studied is an NK cell memory population co-expressing NKG2C and CD57 that expands in blood during human cytomegalovirus (CMV) infection ( 27, 46 ). Multiple putative markers of NK cell memory during Mtb infection have been suggested, including CD57, CD8α, CD161, and CD27 ( 28, 34, 45 ). We compared expression of these markers across clinical groups and found that household-associated LTBI (IGRA+ contacts) and active TB disease donors had progressively decreasing frequency of CD8α + CD56 dim NK cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Prior work provides mechanistic evidence for NK cell recognition of intracellular and extracellular Mtb in vitro through natural cytotoxicity receptor engagement of Mtb cell wall components or stress-induced self-ligands ( 2233 ). However, few published studies directly examine NK cell biology during natural Mtb transmission in humans ( 27, 28, 34 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations